1996
DOI: 10.1093/jmedent/33.3.278
|View full text |Cite
|
Sign up to set email alerts
|

Bionomics of Lutzomyia evansi (Diptera: Psychodidae) Vector of Visceral Leishmaniasis in Northern Colombia

Abstract: The feeding behavior, seasonality, and natural infection rate of Lutzomyia evansi (Nuñez-Tovar) with Leishmania chagasi (Cuna & Chagas) was studied during a 12-mo period at 2 hamlets, El Contento and Vidales. Sand fly abundance in extra-, peri-, and intradomestic habitats was evaluated with sticky traps and CDC light traps, whereas human bait and Shannon trap collections were made only in peridomestic habitats. All trapping methods showed a clear predominance of L. evansi throughout the year. Sand flies were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
16

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 0 publications
2
33
0
16
Order By: Relevance
“…This unimodal pattern of Lu. evansi was similar to that reported in San Andrés de Sotavento, Cordoba Department, Colombia (Travi et al, 1996) where the amount of rainfall was also similar, with a maximum precipitation of about 200 mm. However, indoor col lections of Lu.…”
Section: Leishmania Search and Identificationsupporting
confidence: 88%
“…This unimodal pattern of Lu. evansi was similar to that reported in San Andrés de Sotavento, Cordoba Department, Colombia (Travi et al, 1996) where the amount of rainfall was also similar, with a maximum precipitation of about 200 mm. However, indoor col lections of Lu.…”
Section: Leishmania Search and Identificationsupporting
confidence: 88%
“…In further studies in north Colombia, promastigotes were found in nine more specimens of Lu. evansi and the parasite again identified as L. i. chagasi on two occasions (Travi et al 1996). This, the presence of Lu.…”
Section: Other Possible Vectors Of L I Chagasi In Brazil and Neighbmentioning
confidence: 89%
“…evansi es el vector principal de la leishmaniasis visceral en ausencia de L. longipalpis y se registra como vector de Leishmania infantum en Venezuela y la costa del Caribe colombiano así como en los departamentos de Sucre y Bolívar (17,(21)(22)(23). Recientemente se incrimina como el posible vector de leishmaniasis visceral en zonas rurales de El Carmen de Bolívar (14).…”
Section: Discussionunclassified